2015
DOI: 10.3390/pharmaceutics7040471
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plasma Treatment on Micro-Injection Moulded Microneedle for Drug Delivery

Abstract: Plasma technology has been widely used to increase the surface energy of the polymer surfaces for many industrial applications; in particular to increase in wettability. The present work was carried out to investigate how surface modification using plasma treatment modifies the surface energy of micro-injection moulded microneedles and its influence on drug delivery. Microneedles of polyether ether ketone and polycarbonate and have been manufactured using micro-injection moulding and samples from each producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…Compression tests of PM on a steel plate using Bose Electroforce 3100 instrument with a 225 N load cell and Wintest® software (Bose, MN, USA) revealed that the PMs were able to withstand compression forces of up to 8 N [20].…”
Section: Fabrication and Characterization Of Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression tests of PM on a steel plate using Bose Electroforce 3100 instrument with a 225 N load cell and Wintest® software (Bose, MN, USA) revealed that the PMs were able to withstand compression forces of up to 8 N [20].…”
Section: Fabrication and Characterization Of Pmmentioning
confidence: 99%
“…[19]. In this study, micro-injection moulding was employed for fabrication of the polymeric MN arrays (PM) using PEEK LT-3 (polyether ether ketone) as reported in previous paper [20].…”
Section: Introductionmentioning
confidence: 99%
“…17 . In this study, micro-injection moulding was employed for fabrication of the polymeric MN arrays (PM) using PEEK LT-3 (polyether ether ketone) as reported in Nair et al 18 . The MN mould insert (Fig 2 B) …”
Section: Introductionmentioning
confidence: 99%
“…A microneedle is a short, sharp, spike‐like structure, generally less than 1 mm in length, and is often provided in arrays that may number anything up to several hundred per square centimeter and that can penetrate the epidermal layer of the skin. Although microneedles were originally fabricated using techniques borrowed from the semiconductor industry, injection molding has emerged as a viable alternative for their manufacture, especially as technical advances have facilitated the accurate reproduction of the microscale features associated with microneedles . Furthermore, injection molding is a low‐cost, high‐throughput process that has traditionally been compliant with medical device regulations, materials and manufacturing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Although microneedles were originally fabricated using techniques borrowed from the semiconductor industry, injection molding has emerged as a viable alternative for their manufacture, especially as technical advances have facilitated the accurate reproduction of the microscale features associated with microneedles. 9,10 Furthermore, injection molding is a low-cost, high-throughput process that has traditionally been compliant with medical device regulations, materials and manufacturing procedures.…”
Section: Introductionmentioning
confidence: 99%